Public opinion on MOOCs: sentiment and content analyses of Chinese microblogging data. Issue 2 (25th January 2022) - Zhou, Mingming
ABSTRACT: The increasing and widespread usage of social media enables the investigation of public preference using the web as a device. Public sentiment as expressed in 44, 319 massive open online course (MOOCs) related microblogs from January to December 2017 was examined on Sina Weibo (the Chinese equivalent of Twitter) to obtain broad insight into how MOOCs are viewed by the public in the Chinese educational landscape. Despite the unstable upward trend of public interest in MOOCs over the past 12 months, the public opinion on MOOCs was largely positive. Content and sentiment analyses were conducted to facilitate a better understanding of what is communicated on social media. A general model of public opinions of MOOCs in China has been developed based on the findings. Individuals were classified into a threefold typology based on the sources and purposes of how this recent form of distance education was perceived. Based on the seven themes, the public views towards MOOCs were differentiated among 'promoters', 'commenters' and 'experiencers'.Implications of the findings were also discussed.